Nutrients retention in a small subtropical wetland (México) - Martha B. Rendón-López; M. Luisa Suarez Alonso; Gloria L. Ayala-Ramirez; Yazmin Hernández-Linares; Alberto Gómez-Tagle Chavez; Julio C. Medina-Avila; M. Rosario Vidal-Abarca (Journal of Limnology, 2016)
In tropical areas very few studies have analysed wetlands’ ability to control nutrients. We analysed the efficiency of the Pátzcuaro subtropical wetland in Mexico to retain nutrients (total phosphorus: TP; soluble reactive phosphorus: PO43-, nitrite: NO2- and nitrate: NO3-) and total suspended solids (TSS) and its temporal variability from November 2011 to October 2012, where two hydrological different periods (dry and wet periods) were included. The results indicate that, annually, this wetland reduced TP, 30.4%; PO43-, 19.2%; NO2-, 2.5%; NO3-, 17.6%; and TSS, 14.7%. However, the reduction % rose to 55.3% for TP and to 47.3% for PO43- during the dry period and to 14.1 % for NO2-, 49% for NO3- and 44.5% for TSS during the rainy period. These results show dependence on the hydrological cycle, although P retention is also related with uptake by a dense macrophyte community and with organic matter accumulation. The results obtained suggest that removal of N is due mainly to denitrification. TSS retention seems to respond to low speed hydraulics and the resistance generated by macrophytes roots and floating plants. Like other studies in temperate environments, this wetland seems to remove more efficiently P than N. Unlike that  in temperate environments where the highest nutrient retention occurs in autumn, we found the highest retention values for both NO2- and NO3- during summer (rainy period), and the lowest for P, probably due to release of P for the senescence of wetland plants during this period.